Improving the Third-Year Students’ Reading Comprehension Of English Texts By Using A Speed Reading Technique At Mts Negeri 1 Mojokerto - rR. Heru Winardi (JETS: Journal of English Teaching Strategies, 2022)
The research was planned to improve the third-year students’ reading comprehension of English texts by using a speed reading technique at MTs Negeri 1 Mojokerto. The objectives of the study are to find out how: (1) Speed reading techniques can improve the students’ literal comprehension, and how (2) Speed reading techniques can improve the students’ inferential comprehension. The study was a Classroom Action Research. The procedure of the research consisted of four major steps namely: planning, implementing, observing, and reflecting. This study consists of two cycles. Each of them consists of three meetings for the teaching and learning process and one meeting for posttest. The results of the research showed that speed-reading technique was effective in increasing the students’ reading speed and their reading comprehension achievements. The fact that the average students’ reading speed increased by implementing speed-reading technique. Practically, the result of this study can be used as a model to improve the students’ speed-reading for the sake of improving their reading comprehension skill and their motivation to read as well